2017 International Conference on High Voltage Engineering and Power Systems (ICHVEPS) 2017
DOI: 10.1109/ichveps.2017.8225862
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved gas analysis (DGA) of vegetable oils under electrical stress

Abstract: Dissolved gas analysis (DGA) is often use by the utility companies to monitor the health and to detect any faults of their transformers. The concentration and proportion of various gases dissolved in the oil are used to indicate whether there is an electrical or thermal fault within the transformer. A lot of data have been published in the literature on DGA levels for a mineral oil. However, the data for vegetable oils are relatively sparse even though the vegetables oils have been used for more than 10 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is reported that higher quantities of C 2 H 2 and H 2 are generated in natural esters and C 2 H 2 remains the key gas to indicate a defect or fault witnessed by electrical discharges. Also, the influence of high energy discharges on the gassing tendency of the dielectric fluids have been reported in [14,17,18]. Similar to the low energy discharge faults, H 2 and C 2 H 2 are found to be witnessed due to arcing fault conditions.…”
Section: Introductionmentioning
confidence: 85%
“…It is reported that higher quantities of C 2 H 2 and H 2 are generated in natural esters and C 2 H 2 remains the key gas to indicate a defect or fault witnessed by electrical discharges. Also, the influence of high energy discharges on the gassing tendency of the dielectric fluids have been reported in [14,17,18]. Similar to the low energy discharge faults, H 2 and C 2 H 2 are found to be witnessed due to arcing fault conditions.…”
Section: Introductionmentioning
confidence: 85%
“…In particular, power electronic systems 100 , transformers 101 , batteries 102 , 103 , photovoltaic systems (PV) 104 , 105 , etc. be that as it may, the BPNN model still has several underlying deficiencies, for instance, dull merging speed and over-fitting difficulty 106 , 107 . Fortunately, a significant compilation of optimization processes has been established to optimize the BPNN version, such as Genetic algorithm (GA) 108 111 , Means end analysis (MEA) 112 , Particle Swarm Optimization (PSO) 113 , 114 , Simulated Annealing (SA) 115 , BA 116 , 117 , etc.…”
Section: Applicable Workmentioning
confidence: 99%
“…In [52], the concentration of dissolved gases under electrical performance in vegetable oils – rice bran oil and palm oil – were investigated and compared with mineral oils. From six concentrations of gases contained in the samples (H 2 , CH 4 , C 2 H 6 , C 2 H 4 , C 2 H 2 and CO), C 2 H 2 and H 2 were the highest gases generated due to electrical stress for all the oils.…”
Section: General Differences Between Mineral Oil and Natural Estermentioning
confidence: 99%